2012
DOI: 10.1016/j.crme.2012.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the mixed flow turbine performance under inlet pulsating flow conditions

Abstract: Turbochargers are widely used in Diesel engines as a means of increasing the output power. Most of them are fitted with radial or mixed flow turbines. In applications where high boost pressure is required, radial turbines are replaced by mixed flow turbines which can achieve a maximum efficiency at a lower value of blade speed to isentropic expansion velocity ratio than the usual 0.7 (for radial turbines). This study, performed with the ANSYS-CFX software, presents a numerical performance prediction of a mixed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…The results showed a significant deviation between the hysteresis loop at the rotor inlet during pulsating flow compared to that at steady flow conditions, although the collapse of the hysteresis loop into a single line during the propagation from the volute inlet to the rotor inlet. The former study strongly agreed with that done by Hamel et al [20],…”
Section: Introductionsupporting
confidence: 92%
“…The results showed a significant deviation between the hysteresis loop at the rotor inlet during pulsating flow compared to that at steady flow conditions, although the collapse of the hysteresis loop into a single line during the propagation from the volute inlet to the rotor inlet. The former study strongly agreed with that done by Hamel et al [20],…”
Section: Introductionsupporting
confidence: 92%
“…Hamel and al. [17] conducted a steady and unsteady flow performance analyses and a numerical performance prediction of a mixed flow turbine under inlet pulsating flow conditions. Sakai and al.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, their results showed that the turbine performance is significantly sensitive to the rotational speed. Hamel et al [10] reported the capability of the k-ε turbulence model and the frozen rotor approach to give accurate results of the turbine performance. Karamanis et al [11] investigated on a mixed flow turbine at five different rotational speeds under steady conditions.…”
Section: Introductionmentioning
confidence: 99%